Fitness in antibiotic resistant bacteria - Gillespie, Stephen (Henry Stewart Talks, 2010)
Fitness and resistance, Assessment of growth rate/fitness, Sequential passage methodology, In vivo adaptation, Transmission of strains, Bacteria rapidly adapt